Evaluating the Efficacy of Treatment with a GnRH Analogue in Patients with Central Precocious Puberty - H. Nur Peltek Kendirci; Sebahat Yılmaz Ağladıoğlu; Veysel N. Baş; Aşan Önder; Semra Çetinkaya; Zehra Aycan (International Journal of Endocrinology)
Objective. GnRH analogues (GnRHa) are used in the treatment of central precocious puberty (CPP). The purpose of this study was to evaluate the efficacy of treatment with a GnRHa (leuprolide acetate) in patients with CPP. Subjects and Methods. A total of 62 female child patients who had been diagnosed with CPP, rapidly progressive precocious puberty (RP-PP), or advanced puberty (AP) and started on GnRHa treatment (leuprolide acetate, Lucrin depot, 3.75 mg once every 28 days) were included in the study. The efficacy of treatment was evaluated with anthropometric data obtained, progression of pubertal symptoms observed, as well as GnRHa tests, and, when necessary, intravenous GnRH tests carried out in physical examinations that were performed once every 3 months. Results. In the current study, treatment of early/advanced puberty at a dose of 3.75 mg once every 28 days resulted in the suppression of the HHG axis in 85.5% of the patients. Conclusion. The findings of this study revealed that a high starting dose of leuprolide acetate may not be necessary in every patient for the treatment of CPP. Starting at a dose of 3.75 mg once every 28 days and increasing it with regard to findings in follow-ups would be a better approach.